Childhood adversity and mental health admission patterns prior to young person suicide (CHASE): a case-control 36 year linked hospital data study, Scotland UK 1981–2017 - Ann John (BJPsych Open, 2024)
BackgroundChildhood adversity is associated with increased later mental health problems and suicidal behaviour. Opportunities for earlier healthcare identification and intervention are needed.AimTo determine associations between hospital admissions for childhood adversity and mental health in children who later die by suicide.MethodPopulation-based longitudinal case-control study. Scottish in-patient general and psychiatric records were summarised for individuals born 1981 or later who died by suicide between 1991 and 2017 (cases), and matched controls (1:10), for childhood adversity and mental health (broadly defined as psychiatric diagnoses and general hospital admissions for self-harm and substance use).ResultsRecords were extracted for 2477 ‘cases’ and 24 777 ‘controls’; 2106 cases (85%) and 13 589 controls (55%) had lifespan hospitalisations. Mean age at death was 23.7; 75.9% were male. Maltreatment or violence-related childhood adversity codes were recorded for 7.6% cases aged 10–17 (160/2106) versus 2.7% controls (371/13 589), odds ratio = 2.9 (95% CI, 2.4–3.6); mental health-related admissions were recorded for 21.7% cases (458/2106), versus 4.1% controls (560/13 589), odds ratio = 6.5 (95% CI, 5.7–7.4); 80% of mental health admissions were in general hospitals. Using conditional logistic models, we found a dose-response effect of mental health admissions <18y, with highest adjusted odds ratio (aOR) for three or more mental health admissions: aORmale = 8.17 (95% CI, 5.02–13.29), aORfemale = 15.08 (95% CI, 8.07–28.17). We estimated that each type of childhood adversity multiplied odds of suicide by aORmale = 1.90 (95% CI, 1.64–2.21), aORfemale = 2.65 (95% CI, 1.94–3.62), and each mental health admission by aORmale = 2.06 (95% CI, 1.81–2.34), aORfemale = 1.78 (95% CI, 1.50–2.10).ConclusionsOur lifespan study found that experiencing childhood adversity (primarily maltreatment or violence-related admissions) or mental health admissions increased odds of young person suicide, with highest odds for those experiencing both. Healthcare practitioners should identify and flag potential ‘at-risk’ adolescents to prevent future suicidal acts, especially those in general hospitals.